Persepsi Mahasiswa Islam Penghafal Qur’an Terhadap Jilboobs Sebagai Tren Baru - Melisa paulina; Diana Mutiah (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Jilboobs is a term used to describe women who wear headscarves but show body curves, or in other words Jilboobs is a tight female hijab style. This study aims to look at the student perspectives of those who memorize the Qur'an towards Jilboobs as a new trend. Qualitative method with purposive sampling technique. This study used 6 subjects with certain criteria, namely Islamic students, memorizing the Qur'an, and participating in Islamic studies. Based on the results of the study, it showed that Jilboobs was not in accordance with the proper Islamic studies. For all subjects, even though Jilboobs are considered a new trend, it does not make Islamic students who memorize the Qur'an follow trends because for them the benefits or purpose of wearing the hijab is to cover the genitals (the whole body). For the six subjects, not following the Jilboobs trend did not make him feel out of date, as a memorizer of the Qur'an, it was appropriate to have the morality of the Qur'an by implementing Islamic law and avoiding harm in Islam so that it was an obligation to wear the hijab according to Islamic law